ROVIBRATIONAL SPECTRA OF OPEN-SHELL VANDERWAALS COMPLEXES - AR-OH(X-PI-2) - Chakravarty, C; Clary, D (1991)
A variational basis function approach is described for the calculation of the rovibrational bound states and infrared spectrum of a van der Waals complex of a closed-shell diatom and a 2Π diatom using no angular momentum decoupling approximations. Using an ab initio potential surface, the method is then applied to calculate the bound states and spectra of the system H 2-OH (X2Π), and results are given for the complex containing both para and ortho H2. Interesting similarities and differences are discovered on comparing the results with those for the related Ar-OH and H2-HF complexes. © 1993 American Institute of Physics.